Penerapan Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas 4 di Sekolah Dasar - Dhea Tri Amanda Fiska; Diva Andriani; Adrias Adrias; Fadila Suciana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the effectiveness of the Discovery Learning model in enhancing the motivation and learning outcomes of fourth-grade elementary school students through a literature review. The method used is a literature study, collecting data from various sources, including books, academic journals, and previous relevant research. Data analysis was conducted by examining theories and past research findings regarding the impact of Discovery Learning on student motivation and learning outcomes. The study results indicate that implementing Discovery Learning can increase students' learning motivation by providing a more active and meaningful learning experience. Furthermore, previous research also highlights that this model positively contributes to improving students' academic performance. Thus, Discovery Learning can be considered an effective instructional strategy for enhancing motivation and academic achievement in elementary school students.